The Sustainability of Rural Livelihoods and Ecology among Smallholder Coffee Farmers in the Eastern Districts of Zimbabwe, 1980–2018. (15th September 2019) - Taringana, Takesure; Mtisi, Joseph
This paper examines the sustainability of rural livelihoods and ecology from small-scale coffee production in the Eastern Districts of Zimbabwe from 1980 to 2018. When Zimbabwe attained political independence in 1980, the government made deliberate efforts at encouraging smallholder commercial farming, particularly of coffee in the Eastern Districts of the country. Emphasis on smallholder coffee production was couched within the pitch of black empowerment designed to counter exploitative colonial policies that segregated against blacks. Smallholder commercial agriculture was regarded as the best conduit to improve rural livelihoods and integrate rural economies in the mainstream economic grid, and also to promote environmental protection. Despite efforts invested in the development of smallholder coffee production, livelihoods and ecological sustainability based on the coffee business were elusive and, over time, the sector has failed. A number of factors explain this, including vacillating government policy, organisational challenges, the commodity problem and chronic dependency on donor funding. These developments attract a critical scholarly discourse to analyse livelihoods and ecological sustainability in the coffee business.